Role of neurotransmitters in schizophrenia: a comprehensive study - Videsha Bansal; Indranath Chatterjee (Kuwait Journal of Science)
Schizophrenia is a psychological disorder, way tougher to diagnose than other psychological disorder, as it shares similar symptoms with psychosis. As we know schizophrenia occurs due to chemical imbalance in brain, due to various factors, identification of the role of neurotransmitters in schizophrenia poses an important area to study. Neurotransmitters being the sole carrier of different activities in the brain, researches had initiated studies to investigate its role and effect in the disorder. Firstly, this paper performs the critical review of the literature that dealt with neurotransmitter in schizophrenia. Secondly, here we identify the most important neurotransmitters and broadly elaborates their functional roles and effects on the disorder. Finally, we have successfully identified various gaps and unexplored research questions to investigate the role of these brain chemicals. Studies show that the neurotransmitters like dopamine, glutamate, GABA, serotonin and oxytocin are majorly responsible for schizophrenia, among which dopamine contributes the most. To the best of our knowledge, for the first time this paper encapsulates all the neurotransmitters, enzymes and chemicals, explores their related literature, identifies the most responsible chemicals involve in schizophrenia, and unfolds the unsolved problem for the research community.